2022
DOI: 10.3390/nu15010153
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Low or High Nutrient Intake and Myokine Levels

Abstract: Inadequate nutrient availability has been demonstrated to be one of the main factors related to endocrine and metabolic dysfunction. We investigated the role of inadequate nutrient intakes in the myokine levels of runners. Sixty-one amateur runners participated in this study. The myokine levels were determined using the Human Magnetic Bead Panel from plasma samples collected before and after the marathon. Dietary intake was determined using a prospective method of three food records. The runners with lower car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In support of this hypothesis, musclin levels were unchanged in the CKD group, where no changes in muscle strength or endurance performance were detected. Recently, it has been reported that runners with sufficient carbohydrate intake have higher levels of musclin, which may contribute to improved adaptations to exercise, such as improved glucose homeostasis and browning of adipose tissue [ 34 ]. These findings are again in line with the increased musclin levels and enhanced endurance performance observed in our RD subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this hypothesis, musclin levels were unchanged in the CKD group, where no changes in muscle strength or endurance performance were detected. Recently, it has been reported that runners with sufficient carbohydrate intake have higher levels of musclin, which may contribute to improved adaptations to exercise, such as improved glucose homeostasis and browning of adipose tissue [ 34 ]. These findings are again in line with the increased musclin levels and enhanced endurance performance observed in our RD subjects.…”
Section: Discussionmentioning
confidence: 99%
“…It was also described that higher levels of daily physical activity could decrease circulating FGF21 levels [ 41 ]. Moreover, it has been reported that carbohydrate intake correlates with levels of FGF21 [ 34 ]. In our study, FGF21 levels decreased in the CKD group but remained unchanged in the RD group, suggesting that the effects of the ketogenic diet could have interacted with exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In the original article from Sierra et al [ 17 ], the authors showed the significant effect of adequate energy, sodium, cholesterol, vitamin C, and fiber dietary consumption on exercise-induced myokine production (myostatin, musclin, irisin, BDNF, apelin, IL-15, and FGF-21) in endurance runners, which is important for cardiometabolic adaptations and adequate tissue repair in response to intense physical exercise. The myostatin pathway was also investigated in the work performed by de Carvalho et al [ 18 ].…”
mentioning
confidence: 99%